Vitamin C is effective for the prevention and regression of endometriotic implants in an experimentally induced rat model of endometriosis - Ozlem Ulas Erten; Tuğba Altun Ensari; Berna Dilbaz; Huseyin Cakiroglu; Sadiman Kıykac Altinbas; Muzaffer Çaydere; Umit Goktolga (Elsevier, 2016)
Objective: Endometriosis is a chronic inflammatory disease pathologically defined as the presence of endometrial-like tissue outside the uterine cavity. It is one of the most important diseases affecting women of reproductive age. The process of endometriotic implant growth is mediated by many complex interactions of immunologic, hormonal, genetic, and environmental mediators. Vitamin C (ascorbic acid), besides playing a role in preventing invasion and metastasis, is an antioxidant having anti-inflammatory and -angiogenic effects. In this study, we aimed to investigate the effect of vitamin C on the prevention and regression of endometriotic implants in a rat model of endometriosis. Materials and Methods: This was a prospective, comparative, experimental animal study. After endometriotic implants were induced simultaneously, rats were divided into three groups. Group A was given 500 mg/kg of intravenous vitamin C every 2 days, starting immediately after implantation (n = 11). All rats had a second operation 21 days after the initial one and had the lesion volumes measured. Group B was given 500 mg/kg of intravenous vitamin C every 2 days, starting 21 days after this operation (n = 11). All rats were sacrificed 21 days after the third operation. Implant volume, weight measurements, and histopathological evaluation of the lesions were carried out. Group A received vitamin C throughout the study, while Group C (n = 11) was not given any medication. The findings in the three groups were compared. Results: At the second laparotomy after the induction, Group A had the smallest implant volume with a statistically significant difference compared to Group B (p = 0.012). The end-of-study volumes of endometriotic implants of group B were significantly smaller than the first volumes (p < 0.05). Conclusion: Intravenous vitamin C treatment might have a suppressive effect on the prevention of endometriotic implant induction and regression of endometriotic implant volumes.